Cross-reactive antibodies against dust mite-derived enolase induce neutrophilic airway inflammation. Issue 1 (28th January 2021) - Lin, Jianli; Huang, Nana; Li, Jing; Liu, Xiaoyu; Xiong, Qing; Hu, Chengshen; Chen, Desheng; Guan, Lvxin; Chang, Kexin; Li, Dan; Tsui, Stephen Kwok-Wing; Zhong, Nanshan; et al.
Background and aims: Neutrophilic inflammation is a hallmark of some specific asthma phenotypes; its aetiology is not yet fully understood. House dust mite (HDM) is the most common factor in the pathogenesis of airway inflammation. This study aims to elucidate the role of cross-antibodies against HDM-derived factors in the development of neutrophilic inflammation in the airway. Methods: Blood samples were collected from asthma patients with chronic neutrophilic asthma for analysis of HDM-specific cross-reactive antibodies. The role of an antibody against HDM-derived enolase (EnoAb) in the impairment of airway epithelial barrier function and induction of airway inflammation was assessed in a cell culture model and an animal model. Results: High similarity (72%) of the enolase gene sequences was identified between HDM and human. Serum EnoAb was detected in patients with chronic neutrophilic asthma. The EnoAb bound to airway epithelial cells to form complexes with enolase, which activated complement, impaired airway epithelial barrier functions and induced neutrophilic inflammation in the airway tissues. Conclusions: HDM-derived enolase can induce specific cross-antibodies in humans, which induce neutrophilic inflammation in the airway. House dust mite (HDM)-derived enolase induces cross-antibodies in the body, which recognise both HDM-derived enolase and the enolase in the airway epithelial cells, activate complement and induce neutrophilic inflammation in the airway tissues https://bit.ly/2XKSCgy